The outcomes of tubularized incised plate hypospadias repair and tubularized incised plate grafting using muccal mucosal graft and preputial free graft: a prospective randomized study - Abdelnaser H Mohammed; Ayman Altramsy; Adel Matar; Adel Elbakry (Wolters Kluwer Medknow Publications, 2021)
Objective Hypospadias is the most common anomaly of congenital urogenital defects. Tubularized incised plate (TIP) repair is an established technique. High rates of its complication advocate the idea of grafting of TIP incision. Grafts may be buccal mucosa or prepuce in this study. Patients and methods This prospective study included 64 patients complaining of mid and distal penile hypospadias. The patients were randomized into three groups according to the technique used in the repair of hypospadias. The first group included patients repaired by TIP urethroplasty, whereas group B and group C included patients repaired by inner perpetual skin and buccal mucosa, respectively. Follow-up was for 6 months. Results This study included 64 cases. TIP repair (group A) was done for 20 patients, whereas in 44 cases, TIP grafting was performed; groups B and C included 21 and 23 cases, respectively. The TIP urethroplasty was successful in 85%, whereas in groups B and C, the success rates were 91.5 and 87%, respectively. There were statistically insignificant differences in complications among all groups (P>0.005). Conclusion Outcomes of TIP grafts have no significant difference than outcomes of TIP technique.